Lithium extraction from hard rock lithium ores (spodumene, lepidolite, zinnwaldite, petalite): Technology, resources, environment and cost - Tian-ming Gao; Na Fan; Wu Chen; Tao Dai (China Geology)
Lithium production in China mainly depends on hard rock lithium ores, which has a defect in resources, environment, and economy compared with extracting lithium from brine. This paper focuses on the research progress of extracting lithium from spodumene, lepidolite, petalite, and zinnwaldite by acid, alkali, salt roasting, and chlorination methods, and analyzes the resource intensity, environmental impact, and production cost of industrial lithium extraction from spodumene and lepidolite. It is found that the sulfuric acid method has a high lithium recovery rate, but with a complicated process and high energy consumption; alkali and chlorination methods can directly react with lithium ores, reducing energy consumption, but need to optimize reaction conditions and safety of equipment and operation; the salt roasting method has large material flux and high energy consumption, so require adjustment of sulfate ratio to increase the lithium yield and reduce production cost. Compared with extracting lithium from brine, extracting lithium from ores, calcination, roasting, purity, and other processes consume more resources and energy; and its environmental impact mainly comes from the pollutants discharged by fossil energy, 9.3–60.4 times that of lithium extracted from brine. The processing cost of lithium extraction from lepidolite by sulfate roasting method is higher than that from spodumene by sulfuric acid due to the consumption of high-value sulfate. However, the production costs of both are mainly affected by the price of lithium ores, which is less competitive than that of extracting lithium from brine. Thus, the process of extracting lithium from ores should develop appropriate technology, shorten the process flow, save resources and energy, and increase the recovery rate of related elements to reduce environmental impact and improve the added value of by-products and the economy of the process.©2023 China Geology Editorial Office.